2019
DOI: 10.1136/bcr-2019-231645
|View full text |Cite
|
Sign up to set email alerts
|

Powassan virus encephalitis, severe babesiosis and lyme carditis in a single patient

Abstract: Ixodes scapularis is responsible for transmission of Borrelia burgdorferi, B. miyamotoi, Babesia microti, Anaplasma phagocytophilum and Powassan virus to humans. We present a case of an 87-year-old man who presented with fever and altered mental status. Initial workup revealed haemolytic anaemia, thrombocytopenia, mild hepatitis and acute kidney injury. Patient tested positive for B. burgdorferi and Babesia microti, and was started on doxycycline, atovaquone and azithromycin. He also underwent exchange transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Meanwhile, a study from New York reported that up to 29% of ticks were co-infected with these 2 pathogens. A unique combination of co-infection was recently reported in a case of a patient who had POWV encephalitis, Lyme carditis, and severe babesiosis [ 17 ]. Due to changes in seasonal tick activity compounded by climate change contributing to the expansion of the vector I. scapularis, we may expect to see a significant increase in these infections and co-infections in years to come [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a study from New York reported that up to 29% of ticks were co-infected with these 2 pathogens. A unique combination of co-infection was recently reported in a case of a patient who had POWV encephalitis, Lyme carditis, and severe babesiosis [ 17 ]. Due to changes in seasonal tick activity compounded by climate change contributing to the expansion of the vector I. scapularis, we may expect to see a significant increase in these infections and co-infections in years to come [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…On these patients, five patients had a triple acute active infection [ 11 ]: EM was observed with a proven HGA and TBE. Two more patients were found to have a triple active infection but did not meet the criteria of a confirmed infection [ 12 , 13 ]. For four patients, diagnosis of one of the three infections did not meet the clinical criteria [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…POWVs are rapidly transmitted in tick saliva, cause an acute febrile illness and, in severe cases, encephalitis with long term neurologic damage in patients [1,4,[33][34][35][36][37][38][39][40][41][42] . POWV seroprevalence studies suggest that infections are largely undetected or undiagnosed in patients and this has limited human neuropathology studies.…”
Section: Discussionmentioning
confidence: 99%